Identification of the Challenges of Life Cycle Costing in Green Construction Projects in Malaysia - Maisham, Mysarah; Adnan, Hamimah; Ismail, Noor Akmal Adillah (International Journal of Sustainable Construction Engineering and Technology, 2022)
Concerns on the effect of construction industry to the environment has driven an increase in sustainable construction activities as well as green initiatives. Life cycle costing (LCC) which is a method of assessing the total cost of ownership of an asset or project has been commonly associated with sustainable-related studies and are used around the world for the last few decades. Even though many benefits have been associated with LCC, its implementation in construction industry is still limited, particularly in green construction projects. This paper aimed to identify the main challenges in implementing LCC in Malaysia’s green construction projects. A quantitative approach via questionnaires survey was conducted on 200 respondents from various backgrounds, namely architects, quantity surveyors, engineers and other professionals typically would be involved in LCC preparation for green construction projects in Malaysia. The questionnaires were distributed to the respondents via traditional mail followed by e-mail as well as online platforms in order to increase the response rate. A total of fifty (50) completed and usable questionnaires were collected and analysed based on mean scores and ranking method. It was discovered that the main challenges of LCC in green construction projects were insufficient project or context specific data and difficulties in carrying out LCC calculations due to absent of proper LCC guidelines or framework. The findings serve as a valid point of reference for industry participants concerned with green developments to improve the LCC process and its adoption in Malaysia’s green construction projects. Efforts must be taken to minimize or ease these challenges perhaps by formulating a framework or guideline specifically designed to address the challenges, thus improving the LCC process and encouraging its adoption in Malaysia which will ultimately contribute towards achieving the world’s green construction agenda.